Radiation Tolerant Electronics, Volume II - Leroux, Paul (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Research on radiation tolerant electronics has increased rapidly over the last few years, resulting in many interesting approaches to model radiation effects and design radiation hardened integrated circuits and embedded systems. This research is strongly driven by the growing need for radiation hardened electronics for space applications, high-energy physics experiments such as those on the large hadron collider at CERN, and many terrestrial nuclear applications, including nuclear energy and safety management. With the progressive scaling of integrated circuit technologies and the growing complexity of electronic systems, their ionizing radiation susceptibility has raised many exciting challenges, which are expected to drive research in the coming decade.After the success of the first Special Issue on Radiation Tolerant Electronics, the current Special Issue features thirteen articles highlighting recent breakthroughs in radiation tolerant integrated circuit design, fault tolerance in FPGAs, radiation effects in semiconductor materials and advanced IC technologies and modelling of radiation effects.